Técnicas de construção de dispositivo para obtenção de dados climáticos utilizando sistemas fotovoltaicos - Oliveira, Francisco Jonatham Rocha (Universidade Federal Rural do Semi-Árido, 2019)
In view of the importance of investigating climatic parameters such as temperature and humidity of the air, and to make rainfall forecasts, help in the insertion of urban policies, and prevention of diseases arising from the variations of these parameters, there is a demand for devices capable of collecting data on these variables. In the potiguar upper west, the small research in this area justies the present work, which aims to develop a low cost and free use device that collects data in a continuous and uninterrupted way. In this context, the use of the Arduino microcontroller and the use of solar energy become viable alternatives. Our research aims to present the and environmental engineering. With the calibration of the sensor and the use of the solar panel used in the prototype developed in this work it will be possible to collect data autonomously, with low cost and easy to use.
Keywords: Efeito fotovoltaico; Sustentabilidade solar; Plataforma arduino; Monitoramento ambiental; Fontes alternativas de energia; Photovoltaic effect; Solar sustainability; Arduino platform; Environmental monitoring; Alternative energy sources; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA